A Circularly Polarized Rectangular Dielectric Resonator Antenna Excited by E-Shaped Feed - Iqba, J.; Illahi, U.; I. Sulaiman, M.; Alam, M.; Mazliham, MS. (International Journal of Engineering and Technology, 2018)
This research article present designing and analysis of a novel E shaped feed, which is consisted of seven optimized metallic strips that have been used to excite Rectangular dielectric resonator antenna (DRA) and generate wideband circular polarization. The novel feed has provided a 10-dB impedance matching bandwidth of 7.85% and 3-dB Axial-ratio (AR) bandwidth of 8.12 % in the broadside direction.The proposed DRA attained high gain and beam width i.e. 5.4 dB and 45° respectively over the same frequency range. The model has been simulated in computer simulation technology (CST) software by using the transient solver, based on the finite integration technique (FIT) and thoroughly validated through another computational technique i.e. finite element method (FEM), where a significant trend resemblance can be seen between the results of both solvers.